Establishment of cryopreserved gene banks of European chestnut and cork oak - Vidal, Nieves; Viéitez, Ana M; Fernández, M Rosario; Cuenca, Beatriz; Ballester, Antonio (European Journal of Forest Research, 2010)
Cryopreservation of selected genotypes of European chestnut and cork oak was carried out in two laboratories in a project involving conservation of ﬁeld collections. Plant material was selected on the basis of disease resistance (chestnut), growth habit, phytosanitary performance and cork quality (cork oak). The cryopreservation technique comprised of vitriﬁcation of shoot apices isolated from in vitro stock shoot cultures (chestnut) and somatic embryos (cork oak). Forty-three out of 46 chestnut genotypes assayed survived the freezing process, but only 63% recovered their capacity to produce new shoots. After completion of multiplication and rooting steps, the surviving shoots produced plants that were morphologically identical to those derived from non-supercooled material. All 51 cork oak genotypes withstood freezing and were able to produce new somatic embryos through a process of secondary embryogenesis. Multiplication and germination of the recovered embryos enabled production of plants that were morphologically identical to those derived from nonsupercooled material. In light of the results obtained, longterm cryopreservation of these species is feasible, thereby ensuring conservation of valuable genotypes during ﬁeld evaluation
Keywords: Castanea sativa; Cryopreservation; forest tree species; liquid nitrogen; Quercus suber; Vitrification

El ciclo de biomasa en bosques de frondosas del sur de extremadura. variabilidad espacial del desfronde - TORRES, E; CUEVAS, S; VÁZQUEZ, F Ma; SUÁREZ, Ma A (II Congreso Forestal Español, 1997)
The knowledge of the biomass and nutrients cycle is very important for a suitable forest management. In this paper, four broadleaved species litterfall, during november 1996, is studied in Extremadura (Spain): Castanea sativa Miller, Quercus pyrenaica Willd, Q. rotundifolia Lam and Q. suber L. Litterfall is compared in sorne forests with different maturity. Also, orientation, position and individual tree factors influence is analysed
Keywords: Castanea sativa; Extremadura; litterfall; Quercus pyrenaica; Quercus rotundifolia; Quercus suber

Germination and regeneration mechanisms in Mediterranean degenerate forests - Bacilieri, R.; Bouchet, M. A.; Bran, D.; Grandjanny, M.; Maistre, M.; Perret, P.; Romane, F. (Journal of Vegetation Science, 1993)
Abstract. Germination and developmental behaviour during juvenile stages are of importance in relation to succession mechanisms acting on plant communities. This is particularly so in the Mediterranean region, where the climatic summer drought causes stress. We investigated and compared germination and development of four tree species in two parts of the French Mediterranean region where the original dominant tree species (Quercus pubescens) has been largely replaced by Quercus ilex in the southern part, and Castanea sativa in the northern part. Observed differences in germination rates and developmental behaviour, especially shootroot ratio and the role of water supply, suggest that other species may eventually replace the current dominant species.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Castanea sativa; Pinus pinaster; Quercus ilex; Quercus pubescens

Germination and regeneration mechanisms in Mediterranean degenerate forests - Bacilieri, R; Bouchet, M A; Bran, D; Grandjanny, M; Maistre, M; Perret, P; Romane, F (Journal of Vegetation Science, 1993)
Abstract. Germination and developmental behaviour during juvenile stages are of importance in relation to succession mechanisms acting on plant communities. This is particularly so in the Mediterranean region, where the climatic summer drought causes stress. We investigated and compared germination and development of four tree species in two parts of the French Mediterranean region where the original dominant tree species (Quercus pubescens) has been largely replaced by Quercus ilex in the southern part, and Castanea sativa in the northern part. Observed differences in germination rates and developmental behaviour, especially shootroot ratio and the role of water supply, suggest that other species may eventually replace the current dominant species.
Keywords: Castanea sativa; Pinus pinaster; Quercus ilex; Quercus pubescens

PALYNOLOGY OF A RESIN FROM AN EGYPTIAN COFFIN OF THE 2ND-CENTURY BC - MARIOTTI LIPPI, M; MERCURI, A M (REVIEW OF PALAEOBOTANY AND PALYNOLOGY, 1992)
A palynological analysis was carried out on a small amount of resin from the inside of an anthropoid Egyptian stone coffin from the second century B.C. Pinus halepensis Miller is the best represented resiniferous plant (5.3%) in the pollen spectrum and the botanical origin of the resin can be ascribed to it. The only group of pollen which is relatively abundant in the spectrum is Poaceae (29.6%). This high percentage suggests that grasses were in bloom during the period the resin was collected (late spring or summer). Pollen of Quercus ilex. Olea europaea, Ostrya carpinifolia, Castanea sativa were also found. Pollen grains of Hordeum and Avena/Triticum types together with those of Plantago, Urtica, Chenopodiaceae, Rumex and Artemisia represent anthropogenic indicators. A phytogeographical interpretation of the found pollen assemblage suggests the eastern part of the Mediterranean as the most probable area where the resin was collected. The presence of Cedrus libani pollen suggests an origin from south-eastern Turkey, north-western Syria or northern Lebanon. The flora of this area is in accordance with the pollen assemblage found in the studied resin.
APS
Keywords: Castanea sativa; Ostrya carpinifolia; palynological analysis; Pinus halepensis; Quercus ilex. Olea europaea; resin

PALYNOLOGY OF A RESIN FROM AN EGYPTIAN COFFIN OF THE 2ND-CENTURY BC - MARIOTTI LIPPI, M.; MERCURI, A. M. (REVIEW OF PALAEOBOTANY AND PALYNOLOGY, 1992)
A palynological analysis was carried out on a small amount of resin from the inside of an anthropoid Egyptian stone coffin from the second century B.C. Pinus halepensis Miller is the best represented resiniferous plant (5.3%) in the pollen spectrum and the botanical origin of the resin can be ascribed to it. The only group of pollen which is relatively abundant in the spectrum is Poaceae (29.6%). This high percentage suggests that grasses were in bloom during the period the resin was collected (late spring or summer). Pollen of Quercus ilex. Olea europaea, Ostrya carpinifolia, Castanea sativa were also found. Pollen grains of Hordeum and Avena/Triticum types together with those of Plantago, Urtica, Chenopodiaceae, Rumex and Artemisia represent anthropogenic indicators. A phytogeographical interpretation of the found pollen assemblage suggests the eastern part of the Mediterranean as the most probable area where the resin was collected. The presence of Cedrus libani pollen suggests an origin from south-eastern Turkey, north-western Syria or northern Lebanon. The flora of this area is in accordance with the pollen assemblage found in the studied resin.
APSAPSThe following values have no corresponding Zotero field: pub-location: PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS publisher: ELSEVIER SCIENCE BV
Keywords: Castanea sativa; Ostrya carpinifolia; palynological analysis; Pinus halepensis; Quercus ilex. Olea europaea; resin